Akar Masalah Keamanan Pangan Jajanan Anak Sekolah: Studi Kasus pada Bakso, Makanan Ringan, dan Mi - Dahrul Syah; Mazaya Ghaisani; Suratmono Suratmono; Roy Alexander Sparringa; Nurheni Sri Palupi (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2015)
High consumption of food consumed by school children (PJAS) that are not followed by the application of Good Manufacturing Practices (GMP) potentially lead to many food safety problems. BPOM RI tested a number of PJAS that sold at 3950 elementary schools in Indonesia on 2011-2013 to determine its condition. The result of monitoring only show percentages of complied PJAS (MS/ Memenuhi Syarat) and not complied PJAS (TMS/Tidak Memenuhi Syarat). Further analysis is required to determine the roots of PJAS safety problems and optimal strategy for sustainable improvement of its safety and quality. Data was analyzed with analysis of variance and Pareto diagram. Analysis of variance was used to determine variability between PJAS with provinces as sampling location. It also determined variability between PJAS with food safety parameters. Pareto diagram was used to identify the main problems of food safety parameters on each PJAS. This study focused on meatballs, snacks and noodle products, whereas the other of food product was done separately. According to the result of Pareto analysis, the main problems of PJAS are microbiological contaminant and chemical contaminant. Microbiological contaminant caused by poor sanitation and hygiene on production and preparation process, while chemical contaminant due to misused of hazardous chemicals in food.